The role of kynurenine and kynurenine metabolites in psoriasis - Akyurek Fikret; Tuncez-Akyurek Fatma; Sengul Fatma (Türk Biyokimya Dergisi)
Psoriasis is a widespread immunological disease characterised by inflammation and primarily associated with skin and joint symptoms. The kynurenine pathway significantly influences inflammation and immune system activity. The aim of this study is to determine serum concentrations of kynurenine metabolites in patients with psoriasis and investigate their correlation with disease severity.